Severe osteoarthritis of the hand associates with common variants within the ALDH1A2 gene and with rare variants at 1p31. - Styrkarsdottir, U; Thorleifsson, G; Helgadottir, H; Bomer, N; Metrustry, S; Bierma-Zeinstra, S; Strijbosch, A; Evangelou, E; Hart, D; Beekman, M; Jonasdottir, A; Sigurdsson, A; et al. (2014)
Osteoarthritis is the most common form of arthritis and is a major cause of pain and disability in the elderly. To search for sequence variants that confer risk of osteoarthritis of the hand, we carried out a genome-wide association study (GWAS) in subjects with severe hand osteoarthritis, using variants identified through the whole-genome sequencing of 2,230 Icelanders. We found two significantly associated loci in the Icelandic discovery set: at 15q22 (frequency of 50.7%, odds ratio (OR) = 1.51, P = 3.99 × 10(-10)) in the ALDH1A2 gene and at 1p31 (frequency of 0.02%, OR = 50.6, P = 9.8 × 10(-10)). Among the carriers of the variant at 1p31 is a family with several members in whom the risk allele segregates with osteoarthritis. The variants within the ALDH1A2 gene were confirmed in replication sets from The Netherlands and the UK, yielding an overall association of OR = 1.46 and P = 1.1 × 10(-11) (rs3204689).